Love, Will and Becoming in Vyacheslav Ivanov and Mikhail Bakhtin. (3rd July 2016) - Bosnak, Dmitry
ABSTRACT: The paper discusses the philosophical underpinnings of the ideas of the poet Vyacheslav Ivanov and the philosopher Mikhail Bakhtin. Compared mostly with regard to the Dostoevskian novel, these two authors prove to be connected by a more complex intellectual relationship, as the commentators of Bakhtin's Collected Works have demonstrated. The present paper continues this broad-context discussion by revealing the principal difference between Ivanov's and Bakhtin's worldviews as it stems from the different orders of dependence of love and volition. The framework for comparison is provided by Max Scheler's essay 'Love and Cognition'. The primacy of the will causes constant becoming of the human subject in Ivanov's poetic universe, mostly presented as self-surpassing. The primacy of love in Bakhtin's philosophy of the deed results in the 'becoming' of the other, primarily in the form of the growing value of the beloved, rather than in the form of his or her internal existential transformation.